Syndromes of hematophagocytosis in patients of pediatric intensive care units (literature review) - N. N. Abramova; K. E. Belozerov; G. V. Kondratiev; Yu. S. Aleksandrovich; M. M. Kostik (Вестник анестезиологии и реаниматологии)
Hemophagocytic lymphohistiocytosis (hemophagocytic syndrome, HLH, HPS) is the group of severe life-threatening and hardly diagnosing conditions caused by the immune dysregulation because of systemic inflammatory response with non-controlled proliferation and activation of T-cells, monocytes and macrophages with accumulation in target organs and the development of multiple organ failure. HLH are includes primary (monogenic) and secondary forms associated with various conditions, such as infections, immunopathological, oncohematological diseases. The severity of the condition, association with infections makes these diseases potentially lethal and requiring intensive care. In many critically ill patients in the intensive care unit, the presence of hemophagocytic syndrome remains unrecognized and is often interpreted as generalized infection, sepsis, systemic inflammatory response syndrome, multiple organ failure. Such patients require special attention, timely diagnosis and treatment. Nowadays, we have got a big group of drugs, which can pointwise block one or another pathogenesis pathway, but for a quick and correct choice, we need clear algorithms for deciding on the use of this group of targeted therapy. The article presents the history of the study of the issue and modern approaches to the diagnosis and treatment of these conditions in critically ill patients.